PENERAPAN SQUARE STEPPING EXERCISE DENGAN MASALAH KEPERAWATAN RESIKO JATUH DI PANTI WERDHA BUDI SOSIAL: STUDI KASUS - Yuliana Herawati; Savitri Gemini (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Intrinsic factors causing the risk of falling in the elderly are age, comorbidities such as hypertension, gait disorders, muscle weakness especially in the lower extremities, and a history of previous falls. Extrinsic factors include slippery floors, inadequate lighting, and uneven floors. This study aims to provide the Application of Square Stepping Exercise in Reducing the Risk of Falling in Mrs. I with Instability at the Budi Sosial Foundation Home in Batam City in 2025. The method used in this study is Auto-Anamnesis. The results of the case study research obtained by the author were carried out on Mrs. I through the application of square stepping exercise techniques for 6 days on the first diagnosis of physical mobility disorders related to decreased muscle strength. The second diagnosis of fall risk was proven by the age of 68 years. Balance disorders, decreased muscle strength, and a history of falls. Overcome because on the first day the results of the fall risk assessment were obtained TUG score 16 seconds, which is a high risk of falling, BBS score 34, which is walking with assistance, and the elderly balance assessment score 7, which is a moderate risk of falling. And on the sixth day, the TUG results obtained a score of 11 seconds, which means a low risk of falling, the BBS obtained a score of 41, which means walking independently, and the elderly balance assessment obtained a score of 4, which means a low risk of falling.Keywords: Elderly, Fall Risk, Square Stepping Exercise.